A experiência socioeducativa de internação na vida de jovens em conflitos com a lei - Fialho, Lia Machado Fiuza (2012)
This research relates to a doctoral study conducted in Fortaleza, with a group of young institutionalized in socio unit in compliance with the detention of the practice act qualified as an infraction. The study asks how young people in conflict with the law perceive the experience of hospitalization in their lives. And advocates the thesis that the imprisonment repressive socio along the lines developed in the Educational Center Patativa Assaré (CEPA) precludes the achievement of autonomy and therefore the social rehabilitation of these young people. The scope of the study was to understand the life history of juveniles in conflict with law in internal CEPA considering their perceptions about the meaning of the experience of deprivation of liberty in their trajectories. Aiming at this goal include: discussion was held about the history of assistance to children and adolescents in Brazil to identify changes and continuities characteristics of the current childcare system; problematized the concept of punishment adopted by the State and attendance system socieducativo in Ceará especially given the CEPA, and was related to the perceptions of young people about the hospital with their life stories. To develop the study used qualitative research in the form of a case study in actual field with seven young people under socio hospitalization. Data collection occurred through methodological triangulation (MINAYO, 2005) which used: oral history, recorded and transcribed in full, the field journal, and the medical records as a source of information. Data analysis was conducted by: a technique for generating structure of discourse (FLICK, 2009), which enabled the reading of narratives and communicative validation through appreciation of young people confronting the reports and court reports, contained in records, with accounts who use oral language, and content analysis (Bardin, 1997/2004), to verify the most significant categories in the speech. The results showed negative perception of hospital experience, considered a waste of time. It is suggested to strengthen measures in an open environment, effective public policies to guarantee rights and fighting vulnerable promoting autonomy and support to childcare egress system and develop strategies proposed by the theory of restorative justice.